Use of a helper strain in Neurospora crassa to maintain stocks of uvs-4 and uvs-5, which deteriorate unless sheltered in heterokaryons - David D. Perkins (Fungal Genetics Reports, 1993)
Strains of the mutagen sensitive mutants uvs-4 and uvs-5 that originate from ascospores may initially grow at wild type rate. However, growth becomes slower and progressively more abnormal following vegetative growth (Schroeder 1970 Mol. Gen. Genet. 107:291-304; Newmeyer 1984 Curr. Genet. 9:65-74 and personal communication).